2000
DOI: 10.1515/znc-2000-5-611
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation and Protection of Glycolate Oxidase in vitro and in Leaves

Abstract: Antioxidants, Glycolate Oxidase, PhotoinactivationGlycolate oxidase that was partially purified from pea leaves was inactivated in vitro by blue light in the presence of FMN. Inactivation was greatly retarded in the absence of 0 2. Under aerobic conditions H20 2 was formed. The presence of catalase, GSH or dithiothreitol protected glycolate oxidase against photoinactivation. Less efficient protection was provided by ascorbate, histidine, tryptophan or EDTA. The presence of superoxide dismutase or of hydroxyl r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Functional catalase is crucial for the protection of GOX, which is highly susceptible to oxidative damage (Schäfer and Feierabend, 2000). In support of this notion, we found that the leaf GOX activity in cat2-2 mutants is significantly lower than in the wild type (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Functional catalase is crucial for the protection of GOX, which is highly susceptible to oxidative damage (Schäfer and Feierabend, 2000). In support of this notion, we found that the leaf GOX activity in cat2-2 mutants is significantly lower than in the wild type (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The low GOX activity observed in cat2-2 mutants can be attributed to the preventive role played by the peroxisomal catalase in limiting the degradation of the redox vulnerable GOX cofactor FMN which in its reduced form (FMNH 2 ) contributes to ROS generation (Massey, 1994). Chemically inhibiting catalase with 3-amino-1,2,4-triazole, similarly to the cat2-2 mutation, negatively affects GOX activity (Schäfer and Feierabend, 2000). The crucial role of catalase in maintaining GOX activity seems to be also dependent on the presence of GSH because pharmacologically blocking GSH biosynthesis inactivated GOX even in the presence of catalase (Schäfer and Feierabend, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even this difference disappears within a few hours, so it seems that the vast majority of H 2 O 2 must be metabolized. Although we cannot exclude that some form of down-regulation of H 2 O 2 production through the photorespiratory pathways occurs (Schäfer and Feierabend, 2000), it seems clear that catalase deficiency forces this oxidant through alternative H 2 O 2 -reducing pathways that are less active when catalase capacity is high. As we discuss further below, this notably drives significant changes in cell thiol-disulfide status, as well as adjustments in other areas of metabolism.…”
Section: Hydrogen Peroxidementioning
confidence: 93%
“…DHAR and GR located in the peroxisomal matrix accomplish detoxification of H 2 O 2 produced in the matrix in sequential ascorbate-and glutathione-dependent reactions (Jime´nez et al 1997;del Rı´o et al 1998;Corpas et al 2001). The AA-GSH cycle also provides NAD + for peroxisomal metabolism and GSH protects the flavin-containing oxidases against photoinactivation (Scha¨fer and Feierabend 2000;Corpas et al 2001). Thus, peroxisomes are one of the main cellular organelles where ROS are both generated and detoxified and they appear to be instrumental in redox-homeostasis-mediated defence against abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 99%